Somewhere over the Rainbow - Barbara Grabher (Journal of Festive Studies)
Festival decorations are crucial indicators of the carnivalesque atmosphere of events as they capture celebratory experiences in tangible forms. Due to the strong presence of rainbow colors, LGBT+ Pride events provide fertile grounds for the discussion of decorative materials. While the acclaimed symbol of the rainbow is an expression of the LGBT+ community and their campaign for equality, the color combination is contested due to commercializing and appropriating forces. Next to altered color compositions highlighting particular identities and communities within the LGBT+ spectrum, explorations for alternative decorative patterns and visual expressions inform contemporary celebrations of equality during LGBT+ Pride events. In this article, I begin with a conceptual discussion of the carnivalesque notion, its inherent contradictions of subversion and discipline, and their expression in the form of decorative materials. Through an ethnographic study of the commemorative LGBT50 celebration in the context of Hull UK City of Culture 2017, I argue that alternative decorative approaches not only aesthetically influence the event but enable the reclaiming of the subversive atmospheres produced by the carnivalesque environment. Countering disciplining mechanisms of brand-like rainbow strategies, I outline how artistic practices negotiate innovative approaches to frame LGBT+ communities, identities, and celebrations.